2004
DOI: 10.1023/b:nere.0000018837.27383.ff
|View full text |Cite
|
Sign up to set email alerts
|

Age- and Sex-Dependent Laterality of Rat Hippocampal Cholinergic System in Relation to Animal Models of Neurodevelopmental and Neurodegenerative Disorders

Abstract: Studies suggest age- and sex-dependent structural and functional patterns of human cerebral lateralization underlie hemisphere specialization and its alterations in schizophrenia. Recent works report sexual dimorphism of neurons in the hippocampal formation and specialization of hemispheres in rats. Our experiments indicate for the first time functional lateralization of the high-affinity choline uptake (HACU) system directly associated with a synthesis of acetylcholine in the hippocampus of Wistar rats. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 34 publications
4
24
1
Order By: Relevance
“…of an attenuated left/right asymmetry in the activities of hippocampal choline carriers from 12-week-old control rats separated from nursing mothers for 60-120 min at postnatal days 7 or 14 (Table I) compared to intact animals from our previous work (14) and from this study (controls of Table II) should not be quite surprising. However, 3-10 min separations per day for the first three postnatal weeks are usually used in the above-mentioned studies in contrast to our longer single separation.…”
Section: Separation Of Immature Animals From Nursing Mothers and A Desupporting
confidence: 46%
See 4 more Smart Citations
“…of an attenuated left/right asymmetry in the activities of hippocampal choline carriers from 12-week-old control rats separated from nursing mothers for 60-120 min at postnatal days 7 or 14 (Table I) compared to intact animals from our previous work (14) and from this study (controls of Table II) should not be quite surprising. However, 3-10 min separations per day for the first three postnatal weeks are usually used in the above-mentioned studies in contrast to our longer single separation.…”
Section: Separation Of Immature Animals From Nursing Mothers and A Desupporting
confidence: 46%
“…A comparison of both transport and binding data facilitates a more detailed determination of changes on presynaptic cholinergic nerve terminals. Our previous experiments have demonstrated that the HACU system is sexually dimorphic and functionally lateralized (14). We have observed an enhanced activity of the carriers in the left when compared to the right hippocampus of male but not female rats.…”
Section: Introductionmentioning
confidence: 56%
See 3 more Smart Citations